The Influence of Online Self-Help Groups on Nutrition Management on the Nutritional Status of Cancer Patients Undergoing Chemotherapy - Sulistyawati, Ririn Afrian; Azali, Lalu Muhammad Panji; Nurlaily, Ari Pebru; Mustikarani, Innez Karunia; Faradisa, Elok; Rahmad, Muhammad Nur (http://dharmais.co.id/, 2025)
Background: Chemotherapy can result in toxicity that can affect the nutritional status of cancer patients. Symptoms that are side effects of chemotherapy include anorexia, changes in taste, nausea and vomiting, diarrhea, stomatitis, and constipation, which can lead to inadequate food intake and consequently result in malnutrition in cancer patients. Therefore, this study aimed to investigate the influence of nutrition management of online self-help groups (SHGs) on the nutritional status of cancer patients undergoing chemotherapy.Method: The research results indicated an increase in the number of patients with wellnourished status after the intervention, specifically from 42.9% to 54.3%, with a p-value of 0.046, signifying that there was an impact of the self-help group on the nutritional status of cancer patients.Results: There was a significant influence of online SHGs intervention on the nutritional status of cancer patients undergoing chemotherapy. Therefore, this intervention can be considered as one of the alternatives for improving nutritional management in cancer patients. Conclusion: The identification of CA-125 levels in diagnosing ovarian cancer in ovarian tumor patients with suspected malignancy was a promising test with high diagnostic accuracy levels.